2018
DOI: 10.1126/scitranslmed.aat3504
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of activin signaling in lung adenocarcinoma increases the therapeutic index of platinum chemotherapy

Abstract: Resistance to platinum chemotherapy is a long-standing problem in the management of lung adenocarcinoma. Using a whole-genome synthetic lethal RNA interference screen, we identified activin signaling as a critical mediator of innate platinum resistance. The transforming growth factor-β (TGFβ) superfamily ligands activin A and growth differentiation factor 11 (GDF11) mediated resistance via their cognate receptors through TGFβ-activated kinase 1 (TAK1), rather than through the SMAD family of transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Many theories have been proposed to explain resistance and researchers are tirelessly seeking strategies to overcome it. Using a whole-genome synthetic lethal RNA interference screen, Marini et al identified that the Activin pathway is essential for platinum resistance [ 107 ]. Blocking activin and growth differentiating factor 11 can significantly improve platinum induced cancer cell death.…”
Section: Shh Pathway and Resistance To Chemotherapymentioning
confidence: 99%
“…Many theories have been proposed to explain resistance and researchers are tirelessly seeking strategies to overcome it. Using a whole-genome synthetic lethal RNA interference screen, Marini et al identified that the Activin pathway is essential for platinum resistance [ 107 ]. Blocking activin and growth differentiating factor 11 can significantly improve platinum induced cancer cell death.…”
Section: Shh Pathway and Resistance To Chemotherapymentioning
confidence: 99%
“…In order to directly compare the response of lung adenocarcinoma cells to the continuous presence of cisplatin, or a pulse of cisplatin that mimics in vivo pharmacokinetics (2h, 5 μg/mL) ( Figure 1A), we monitored the growth and apoptosis of the innately resistant A549 lung adenocarcinoma cell line (Marini et al, 2018) by live cell imaging under both conditions ( Figure 1B). This analysis demonstrated that while continuous exposure to cisplatin resulted in decreased cell number and increased apoptosis over 72h, a pulse of cisplatin only reduced the rate of cell proliferation and did not induce apoptosis.…”
Section: Continuous Versus Pulsed Cisplatin Treatmentmentioning
confidence: 99%
“…To further examine the differences between these two models, we used multiplexed, bead-based protein analysis to investigate the DNA damage, apoptotic and signalling response for key pathway components previously implicated in the response to continuous cisplatin exposure (I.e. p38, ERK, JNK and MCL-1) (Marini et al, 2018, Stewart, 2007 (Figure 1C, Supplementary Figure 1). As might be expected, the continuous exposure model resulted in a significantly elevated and sustained DNA damage response when compared to the pulse model, particularly for the phosphorylation of Chk2 (Ser345), p53 (Ser15 and Ser46), pH2A.X (Ser139 -γH2A.X) and expression of p21 and MDM2.…”
Section: Continuous Versus Pulsed Cisplatin Treatmentmentioning
confidence: 99%
See 2 more Smart Citations